2011
DOI: 10.1590/s1678-77572011000600014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfur-based hemostatic agents and gingival retraction cords handled with latex gloves on the polymerization of polyvinyl siloxane impression materials

Abstract: ObjectivesThis study investigated the possible interactions between three addition silicone materials (Express®, Aquasil Ultra® and Adsil®), three hemostatic agents (ferric sulfate, StatGel FS®; aluminum sulfate, GelCord®; and aluminum chloride, Hemostop®) and gingival retraction cords previously handled with latex gloves to determine whether direct contact with medicaments or indirect contamination by latex in conditions similar to those found in clinical practice inhibit or affect the setting of the impressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Retardation on polymerization of impression materials after sulfur-based gingival retraction agents has been previously demonstrated. 9,15 Claims have been attributed to the effect of sulfur radicals. Although Expasyl does not contain sulfur, retardation has also been shown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Retardation on polymerization of impression materials after sulfur-based gingival retraction agents has been previously demonstrated. 9,15 Claims have been attributed to the effect of sulfur radicals. Although Expasyl does not contain sulfur, retardation has also been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a significant difference on the setting of PVS materials when contaminated with Expasyl and interim prosthodontic materials . However, there is also an alternative view with contradictory results . This suggests that in addition to variations in experimental methods, the effect may be material‐ and brand‐related …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of this, AlCl 3 used at concentrations of over 10% 6 may cause tissue destruction and permanent gingival recession of 0.1 mm 9 . According to Tarighi, Khoroushi 8 (2014), AlCl 3 may interact in the polymerization process of polyvinyl siloxane-based (addition silicone) materials, however, this fact has been refuted by some authors who claim that there is no such correlation 10 .…”
Section: Introductionmentioning
confidence: 99%